Participación y representatividad de los religiosos en el gobierno del propio Instituto. Reflexión a los cincuenta años del Concilio Vaticano II - Marcelo Gidi Thumala, S. J. (Estudios eclesiásticos, 2012)
The acts of governance are an instrument of unity and communion in the care of the charism and patrimony of the Religious Institute on behalf of all its members. Religious life for the Church remains a «anticipation» of the Holy Spirit. As a charismatic event it has characterized itself for offering new inspirations vis-à-vis the permanent challenges of evangelization, which have materialized in new institutions. Without diminishing the personal authority of the superior, with ingenuity and adaptation, we now find new styles of governance in religious institutes. This article will address the Book II, Part III, Section 1, Title 2, Chapter 2 of the Code of Canon Law/83, which deals with the «Governance of Institutes». We want to show how, in Religious Institutes, saving the necessary and indispensable principle of personal authority of superiors, the various chapters, councils, committees, meetings and other participatory bodies continue on the path of renewal to which Vatican II Council invited them.